2021
DOI: 10.1186/s12868-021-00662-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of common genetic variation and biological pathways in autism spectrum disorder

Abstract: Background Autism spectrum disorder (ASD) is a complex neurodevelopmental condition characterized by persistent deficits in social communication and interaction. Common genetic variation appears to play a key role in the development of this condition. In this systematic review, we describe the relationship between genetic variations and autism. We created a gene dataset of the genes involved in the pathogenesis of autism and performed an over-representation analysis to evaluate the biological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…The two most common NDDs among children are attention-deficit/hyperactivity disorder (ADHD) diagnosed in 5-10% and autism diagnosed among 1-3%, of children globally [2][3][4]. Several of the risk factors are known including (epi-)genetic, environmental, and psychosocial factors including pre-and perinatal factors such as preterm birth, pollutants, dietary factors and parental characteristics (obesity, age)-yet familial confounding makes it difficult to establish independent effects [2][3][4][5]. However, evidence indicates that exposure to systemic antibiotics during the developmental phase (and in early life) may pose a risk factor for these disorders through mechanisms grounded in the gut microbiome [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The two most common NDDs among children are attention-deficit/hyperactivity disorder (ADHD) diagnosed in 5-10% and autism diagnosed among 1-3%, of children globally [2][3][4]. Several of the risk factors are known including (epi-)genetic, environmental, and psychosocial factors including pre-and perinatal factors such as preterm birth, pollutants, dietary factors and parental characteristics (obesity, age)-yet familial confounding makes it difficult to establish independent effects [2][3][4][5]. However, evidence indicates that exposure to systemic antibiotics during the developmental phase (and in early life) may pose a risk factor for these disorders through mechanisms grounded in the gut microbiome [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A study comparing four animal models for autism confirmed an increased E/I ratio due to hyperexcitability and reduced feedforward inhibition (62). A recent systematic review focusing on common genetic variation in autism also confirmed alterations in genes involved in the synthesis of GABA-A receptors as well as both ionotropic and metabotropic glutamate receptors (63). Here we showed that genetic variation was associated with glutamate concentrations in the ACC, a region implicated in autism and related phenotypes (64)(65)(66) as well as a region where glutamate concentrations have consistently been reported to be associated with autism before (7,8,23,67).…”
Section: Discussionmentioning
confidence: 88%
“…The gene that encodes TPH , a rate-limiting enzyme for 5-HT synthesis, has been associated with ASD and other neurological disorders [ 223 , 224 ]. Moreover, a systematic review of common genetic variation in ASD showed that enriched pathways in the over-representation analysis are mostly associated with neurotransmitter receptors and their subunits, including 5-HT, GABA, and glutamate receptors [ 225 ]. During brain development, 5-HT has been shown to modulate numerous events, including cell division, neuronal migration, cell differentiation, and synaptogenesis, even before it becomes important as a neurotransmitter [ 226 , 227 ].…”
Section: Perinatal Kp Metabolismmentioning
confidence: 99%